2015
DOI: 10.1155/2015/896507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gingival Microleakage in Class II Composite Restorations with Different Lining Techniques: An In Vitro Study

Abstract: Aim. To compare the microleakage in class II composite restorations without a liner/with resin modified glass ionomer and flowable composite liner. Method. Forty standardized MO cavities were prepared on human permanent mandibular molars extracted for periodontal reasons and then divided into 4 groups of ten specimens. The cavity preparations were etched, rinsed, blot dried, and light cured and Adper Single Bond 2 is applied. Group 1 is restored with Filtek P60 packable composite in 2 mm oblique increments. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…In theory, it seems that using a liner of flowable composite or RMGI with more wetability that causes better adaptation of restoration to cavity walls, and also with reduction of the C-factor, will lead to fewer cavity wall stresses, and subsequently less microleakage, as several studies have shown. [ 3 6 9 14 17 26 ] In contrast, some studies, including the present one, have indicated that the use of flowable material as an intermediate layer does not reduce microleakage in composite restorations. [ 7 10 27 28 ] They have explained that flowable composites have higher polymerization shrinkage due to their lower filler content and this may disrupt the bond to the cavity walls.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In theory, it seems that using a liner of flowable composite or RMGI with more wetability that causes better adaptation of restoration to cavity walls, and also with reduction of the C-factor, will lead to fewer cavity wall stresses, and subsequently less microleakage, as several studies have shown. [ 3 6 9 14 17 26 ] In contrast, some studies, including the present one, have indicated that the use of flowable material as an intermediate layer does not reduce microleakage in composite restorations. [ 7 10 27 28 ] They have explained that flowable composites have higher polymerization shrinkage due to their lower filler content and this may disrupt the bond to the cavity walls.…”
Section: Discussionmentioning
confidence: 68%
“…Some other studies have shown the same results. [ 16 17 26 27 ] They showed that use of flowable composite light cured simultaneously with the main composite did not improve marginal sealing, in contrast with other studies, which hypothesized that co-curing the flowable liner and the overlying composite together would help to improve the penetration of uncured liner and leads to improved sealing at the margin due to hydraulic pressure of the overlying viscous composite. [ 6 15 ] This may be explained by displacement of flowable composite into the main bulk of the composite, which leads to a heterogeneous increase of resin contents of the main bulk of the composite restoration and subsequently, an increase of polymerization shrinkage and microleakage.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Gowda et al (2015) 63 evaluated flowable composite and resin modified glass ionomer (RMGI) in terms of microleakage and found that specimens with flowable composite liner showed statistically better seal compared to RMGI liner group and contributed their results to the fact that there is minimal internal porosities incorporated within the material. On top of that, the intimate fit of flowable composite to the prepared cavity provides a profound bond with the microstructural defects of the cavity preparation, moreover, flowable composite with a low modulus of elasticity and/or surface tension and increased flexibility would have rearranged the stresses accompanied with polymerization shrinkage and retained bond integrity to tooth structure 64 .…”
Section: These Results Agreed With Spreafico Et Al (2016)mentioning
confidence: 99%
“…Polymerization shrinkage, missing elastic deformation, increased viscosity and porosities could be the cause of increase microleakage in RMGIC [ 49 ]. The other reason of microleakage could be dual setting characteristics of RMGIC compared to SDR which is light cure [ 50 ].…”
Section: Discussionmentioning
confidence: 99%